The Flint Industry of Naḥal Zehora I, a Wadi Raba Site in the Menashe Hills - Gopher, Avi (Bulletin of ASOR, 1989)
This article analyzes the flint assemblage from Naḥal Zehora I, a single-component site containing pottery identified as "Wadi Raba." Technological and typological characteristics are quantitatively described and attention is drawn to the presence of the "old-new" chamfered pieces. By comparison with other assemblages, a mid-fifth millennium B. C. date is suggested for this assemblage.